2017
DOI: 10.1007/s11884-017-0407-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of the Underactive Bladder: Evolving New Concepts

Abstract: Purpose of Review Underactive Bladder (UAB) is an emerging concept of voiding dysfunction, building on a tradition of often overlapping and confusing terminologies describing the patient experience, urodynamic function, and pathophysiology. This confusion of symptoms with function with pathology has hampered development of an effective disease model. Recent Findings As with other urinary symptoms, the relationship of voiding symptoms to urodynamic dysfunction is variable. Efforts are underway to formally def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…The various causes of underactive bladder were reported. It mostly involved myogenic failure, efferent or afferent nerve dysfunction and central nerve system (CNS) dysfunction [ 13 , 14 ]. Human interconnected detrusor muscle bundles extend from the bladder to the bladder neck and urethra as an integrated unit [ 15 ].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…The various causes of underactive bladder were reported. It mostly involved myogenic failure, efferent or afferent nerve dysfunction and central nerve system (CNS) dysfunction [ 13 , 14 ]. Human interconnected detrusor muscle bundles extend from the bladder to the bladder neck and urethra as an integrated unit [ 15 ].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Idiopathic causes, cardiovascular insults, and neurogenic causes may all underlie eventual development of UAB through the previously described pathophysiologic pathways. [ 15 16 ] A recent retrospective study of 1726 patients believed to suffer from UAB found that based on patient history, 11.5% of patients would fall into the idiopathic subclass, with neurogenic causes accounting for 84.6% and myogenic causes 2.6%. [ 5 ] However, a 2016 retrospective study of 4 years of patients with UAB at one institution was unsuccessful in finding a correlation between clinical and urodynamic variables and etiologies of UAB.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…O termo DU, foi primeiro usado por Abrams em 1980 (74) . O termo UAB é um diagnóstico de urodinâmica (75) . Dificuldade e confusão surgem no diagnóstico correto do DU, pois no momento, ele só pode ser definido com precisão com base na pressão urodinâmica de fluxo, onde se usa o índice de contratilidades vesical (BCI), BCI= pdetQmax + 5Qmax (57,76,77) .…”
Section: "Síndromeunclassified
“…, Acredita-se que, alterações na sinalização aferente representa um papel principal (3,27,38,57,75,79,80) .…”
Section: "Síndromeunclassified